Abrasive Wear Characteristics of the Coating Area of A Low Carbon Steel Surface Alloyed Through A Tungsten Inert Gas Welding Process”. Surface Engineering - Korkut, Mehmet H.; Gök, M.s. (My University, 2009)
Bu bilimsel makalede, Düşük karbonlu çeliğin yüzeyi TIG metodu kullanılarak farklı alaşımlarla kaplanmış ve abrasiv aşınmaya karşı olan etkileri ve mikroyapı özellikleri incelenmiştir. Yine çalışmada birçok kaynak parametresi kullanılmıştır. Kaplanan bölgenin yüzeyi ve yüzey altı mikroyapı değişiklikleri detaylı incelenmiştir. Ayrıca bu çalışma da elde edilen bulgular SEM, EDS ve X-Ray çalışmaları gibi ileri araştırma teknikleri kullanılarak sonuçlar desteklenmiştir

Low carbon steel surfaces were alloyed with composite powders using the tungsten inert gas welding method. After the alloying process, the effects of welding parameters, such as energy input, progress speed and coating thickness on the microstructural characteristics of the alloyed samples were examined. In the experimental investigation, a low carbon steel surface was alloyed with austenitic stainless steel powder and austenitic stainless steel composites mixed with 4?5% Co, Mo and Ti particles respectively. Following surface alloying, conventional characterisation techniques, such as optical microscopy, scanning electron microscopy, energy dispersive spectrograph and X-ray diffraction, were used to study the microstructure of the alloyed zone. Hardness measurements were also performed across the alloyed zone. Examination of the microstructure revealed the presence of M23C6 carbides, solid melt phases, and intermetallic phases, such as Ni3Ti, depending on the alloying element in the composite. As the amount of the reinforcing material increased, the saturation rates for the samples decreased, while their hardness increased. The abrasive wear tests conducted revealed that temperature input plays a significant role on the microstructure characteristics, which positively affected the abrasive wear values of the samples. Consequently, the tungsten inert gas welding method was successfully used for the surface alloying of low carbon steels.
Bildiri - Yayımlanmış
Makale - Yayımlanmamış Makale
Keywords: Abrasive Wear Coating Steel Surface Alloyed Tungsten Inert Gas Welding Surface Engineering